Preventable hospital admissions related to medication (HARM): Cost analysis of the HARM study - Leendertse, Anne J.; Van Den Bemt, Patricia M.L.A.; Poolman, J. Bart; Stoker, Lennart J.; Egberts, Antoine C.G.; Postma, Maarten J. (Value in health, 2011)
Adverse drug events (ADEs) can cause serious harm to patients and can lead to hospitalization or even death. ADEs are a burden not only to patients and their relatives, but also to society and have the potential to involve high costs. To provide more information on the economic burden of preventable adverse drug events of outpatients, we performed a cost study on the data collected in the Hospital Admissions Related to Medication (HARM) study. In this study we examined the frequency, preventability, and risk factors for hospital admissions related to medication. The average costs for a preventable medication-related hospital admission were calculated by summing the direct medical costs and the production losses of all the preventable admissions, taking into account the different types of hospitals (academic and general) and the age of the admitted patients. The average medical costs for one preventable medication-related hospital admission were €5461. The average production loss costs for one admission were €1712 for a person younger than 65 years of age. Combining the medical costs and the costs of production losses resulted in average costs of €6009 for one, potentially preventable, medication-related hospital admission for all ages. The costs of potentially preventable hospital admissions related to medication are considerable. Therefore, patient safety interventions to prevent ADEs and hospital admissions may be cost-effective or even cost saving.